Museums and written communication : tradition and innovation - Winterbotham, Nick; Avagyan, Ani (Cambridge Scholars Publishing, 2018)
This volume brings together 30 museum experts (26 in English and 4 in French) to lift the lid on museum print and texts. Contributions were originally presented at the UNESCO World Book Capital of 2012, a timely and far-sighted conference held in Armenia. If text is essential to communication, how can museums be sure that what they offer will engage, interpret or even transform the visitor, the tourist or the scholar? This book offers a wealth of answers to this question and related concerns.